Evaluation of HiCrome KPC Agar for the Screening of Carbapenem-Resistant Enterobacterales Colonization in the ICU Setting of a Tertiary Care Hospital - Mahapatra, Ashoka; Nikitha, K; Rath, Sutapa; Behera, Bijayini; Gupta, Kavita (Journal of Laboratory Physicians, 2021)
Background Spread of carbapenem-resistant Enterobacterales (CRE) is a significant concern in intensive care unit (ICU) settings. Approaches to routine screening for CRE colonization in all ICU patients vary depending on institutional epidemiology and resources. The present study was aimed to evaluate the performance of HiCrome Klebsiella pneumoniae carbapenemase (KPC) agar for the detection of CRE colonization in ICU settings taking the Centers for Disease Control and Prevention (CDC) recommended method as reference.Methods Two-hundred and eighty rectal swabs (duplicate) from 140 patients were subjected to CRE detection in HiCrome KPC agar and MacConkey agar (CDC criteria).Results Using CDC method, total 41 CRE isolates were recovered comprising of 29 Escherichia coli, 11 Klebsiella, and 1 Enterobacter spp. On the other hand, 49 isolates of CRE recovered from 140 rectal swabs using HiCrome KPC agar, out of which 33 were E. coli, 15 Klebsiella, and 1 Enterobacter sp.Statistical Analysis Sensitivity, specificity, negative, and positive predictive values of CRE screening by HiCrome KPC agar were found to be 100% (91.4–100), 91.9% (84.8–95.8), 83.6% (70.9–91.4), and 100% (95.9–100), respectively, taking the CDC recommended method as reference.Conclusion HiCrome KPC agar has high sensitivity in screening CRE colonization. Further studies are needed to establish its applicability for detecting the predominant circulating carbapenemases in the Indian setting.
Keywords: CRE; HiCrome KPC agar; rectal swab